Isolating chitin and derivatizing chitosan from dead adult black soldier fly - Ng, Khai Xi (2023)
Insect, particularly black soldier fly can be a potential source of chitin and chitosan. In this study, dead adult black soldier fly bio-wastes was evaluated for its production of chitin and chitosan to add value to the waste. The sample was dried, sieved, grinded and defatted prior to the chitin extraction. The chitin which was extracted through chemical demineralization followed by deproteination, obtained the yield in dry weight basis of 10.44 ± 1.39%. The yield dropped to 5.70 ±0.11% after decolorization, and a color change from dark to white was observed. The obtained chitin yield suggested milder condition was better for chitin extraction from BSF, coupled with high yield, high demineralization and deproteinization efficiency and shorter experimental time. The chitin content of dead adult BSF and extracted chitin were determined as 10.88 ± 0.18 and 36.52 ± 1.08 mg/g respectively. The low determined chitin content suggests a harsher acid hydrolysis treatment should be used to completely digest the chitin to glucosamine prior to spectrophotometric measurement. The extracted chitin was converted to chitosan I and II using two levels of deacetylation with the same NaOH concentration (12.5 M), 80ºC for 15 h for chitosan I and 50ºC for 6 h for chitosan II, with the occurrence of different extent of browning. The yield of chitosan I and II were 3.78 ± 0.16% and 3.79 ±0.25% respectively. Commercial, pharmaceutical and chitosan I and II were compared using FTIR. As a result, iii chitosan I and II exhibited a similar structure with commercial chitosan, with the presence of characteristic functional groups including amide I, amide III, C-O stretching and C-O-C asymmetric stretching that indicated as primary amino group at C2 position, as well as the presence of C-H bending and CH3 symmetric deformation that was not observed in pharmaceutical chitosan. Both chitosan I and II were showed a high degree of deacetylation of 80.90 and 80.70%, suggested milder deacetylation temperature and short reaction time of 6 h is sufficient to obtain a high DDA (~80%) to indicate promising deacetylation on the chitin of BSF. This study reported that significant amount of chitin and chitosan could be extracted from dead adult BSF bio-wastes even with mild extraction condition, and the chitosan had similar characteristic with commercial chitosan from crab shell which suggested its used as alternative chitin and chitosan source